Análise ambiental da Bacia Hidrográfica do Rio Pinheiros (Município de Orleans e São Ludgero, SC), com base na caracterização e diagnóstico dos elementos da paisagem e da perda de solo por erosão laminar - Marcomin, Fátima Elizabeti (Universidade Federal de São Carlos, 2002)
The environmental analysis of the Pinheiros River watershed basin was performed by means of characterization and diagnosis of the landscape factors (altitude, slope, road net, land use and type of soil) and soil loss by sheet erosion, applying this approach to fourteen subunits of landscape managing delimited on the study area. The soil loss evaluated and based on the Universal Soil Loss Equation (USLE), the factors making part it and the landscape structural factors were generated by the Geographical Information System (GIS) IDRISI v.2.0. Soil losses lower than 10t/ha/year predominated over the landscape subunits, being that values of soil loss, corresponding to 242.3 and 39.1 t/ha/year, were evaluated for the subunits Pinheiros River B.E and Barreira , respectively. The Barreira subunit corresponded to that of lower environmental quality risky exposure in relation to the use and soil loss, once it shows a higher percentage of vegetation area, a lower percentage of cultivation area as well as a lower average value soil loss. Pinheiros Alto River B.E. and Boa Vista , were the most exposed subunits, and where the highest a average values take place; the latter one is also that with a higher cultivation area. The integrated analysis between the soil loss (high and very high classes), are associated with the cultivation areas. Around 23% of the Pinheiros River watershed basin total area reveal soil losses above the tolerance limit, signaling the need for review concerning the soil use types and soil handing in the hope of reducing the impact effects from the erosion.
Keywords: Ecologia; Ecologia da paisagem; Erosão do solo; Sistema de informação geográfica; Bacia hidrográfica; USLE; Soil erosion; Watershed basin; Landscape ecology; GIS; CIENCIAS BIOLOGICAS